Elements of Global Environmental Democracy - Agarwal, Anil (Indian Forester, 1992)
Environmental problems can be divided into two categories namely those which can be managed by local communities and the second category includes those problems which can be managed at global level. Both types of problems need support of local community, national as well as global. Environmental problems can be solved by new concepts of citizenship, global compactness and community, national and global environmental democracy. Environment can be protected in a better way by providing global right for survival, information, atmosphere and appropriate compensation for community biological knowledge.